Danton - Przybyszewska, Stanisława 1901-1935; Prodromidès, Jean 1927-; Przybyszewska, Stanisława 1901-1935; Przybyszewska, Stanisława 1901-1935 (Criterion Collection, 2009)
Georges Danton, the popular revolutionary leader, returns to Paris at a time when the new Republic is in disarray. Robespierre and his allies have set up a monstrous dictatorship, beginning the infamous "Reign of Terror." Danton pleads with the people for an end to the bloodshed which violates the spirit of their revolution.
Aspect ratio 1.66:1, 16:9 widescreen. - New, restored high-definition digital transfer
Orig.: Frankreich, Polen, Bundesrepublik Deutschland 1983
Enth. original theatrical trailer ; video interviews with director Andrzej Wajda, screenwriter Jean-Claude Carrière, and Polish film critic Jerzy Plazewski ; Wajda's "Danton," a 42-minute behind-the-scenes documentary on the making of the film ; a booklet featuring a new essay by film scholar Leonard Quart
Keywords: Danton, Georges Jacques <1759-1794> -- Drama; Przybyszewska, Stanisława <1901-1935> -- Film adaptations; Robespierre, Maximilien <1758-1794> -- Drama; Geschichte; Revolutionaries -- France -- Drama; Frankreich; France -- History -- Reign of Terror, 1793-1794 -- Drama; Biographical films; Feature films; Fiction films; Film adaptations; Foreign films; Historical films; Motion pictures, French